The Formation of a Career Trajectory by Students of Secondary Vocational Education in the Russian Arctic Zone - Anna V. SIMAKOVA (Arctic and North, 2021)
The purpose of the article is to identify the features of professional self-determination and formation of career trajectories of secondary vocational education students in the subjects of the Russian Arctic zone, their orientation towards professional implementation in the Arctic zone of Russia. The study is based on the survey of secondary vocational education students in the constituent entities of the Russian Arctic zone in the framework of the All-Russian career guidance lesson “Start your career in the Arctic and the Far East!”. A total of 686 questionnaires of respondents from Krasnoyarsk Krai, Murmansk Oblast, Komi Republic and the Republic of Sakha (Yakutia) were selected for analysis. The results of the study showed that only about a third of students have decided on further plans for building career trajectories. Most students, when shaping their professional future, are guided by personal desires and preferences, as well as by material well-being. Every tenth student does not clearly associate his/her future with employment in the specialty. About a third of students are focused on professional implementation in the Russian Arctic zone. The results of the study can be useful for researchers, specialists in professional self-determination, teachers and consultants of educational institutions of secondary vocational education, as well as authorities in the field of education, labor and employment.